Uma professora de língua inglesa de escola pública: suas representações e práticas pedagógicas - Natália Mariloli Santos Giarola (2016)
This paper approaches teachers education in Applied Linguistic area in order to analyze sayings through The Theory of Enunciation crossed by Freudo-Lacanian psychoanalysis. In this approach, the subject is heterogeneous, divided by the unconscious and affected by language, aiming at wholeness and unity that are impossible, but they allow questioning and transformation. The teacher goes through identity shifts when they seek to become a foreign language teacher and start to self-identify as having knowledge that distinguishes from the others. In this work, we focus on some representations of an English teacher from a public school in the region of Contagem-MG about herself as an educator, her students, the researcher, the school system, her own teaching practice and the continuing education program. The instruments used for the corpus formation were teachers daily notes, semi-structured interviews, classroom observation and field notes. The corpus were organized from themes that emerged in the teachers sayings. Then, we noticed that the educator represents herself as frustrated and dissatisfied with her own English knowledge, the teachers devaluation, and lack of authority in the classroom. She also compares herself with other teachers, aiming to approach an image of herself as more proficient and more prepared methodologically. In addition, Sofia oscillates between the looking time and the understanding time, that is, time to interrogate and seek linguistic and methodological improvement that she wants. The continuing education environment is represented with a space that helps teachers know new teaching methods and deal with the problems encountered in the classroom. In addition, for English teaching, the teacher uses games and develops projects in order to win her students over, because indiscipline is a recurring complaint in her words. Then, this study may contribute to discuss teachers education because we discuss relevant issues that may make teachers confront the representations that they give themselves as they consider themselves teachers and speakers of English.